Political Activism and Family Matters in Nadine Gordimer‘s My Son’s Story (1990) - Babacar Diakhaté (Budapest International Research and Critics University, 2021)
Before independence, South Africa experienced her most socio-political turbulences because of Apartheid. Peter Abrahams, John Maxwell Coetzee and Nadine Gordimer depict racial discrimination, political and sexual violence and social injustice in the context of Apartheid. The aims of this article is to portray “political affairs”, “family matters” and private passions in Nadine Gordimer’s My Son’s Story. It also brings to light Sonny’s motivation to become a political activist and join the blacks in the resistance against racial discrimination.